Socialization of younger students: updated priorities and content characteristics - Zarina I. Cherginskaya (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper presents theoretical and methodological grounds that enhance the development of updated priorities and content characteristics of socialization of younger students. Problems and risky situations of social formation of growing subjects have been identified. The analysis of the main regulatory documents is presented, which makes it possible to actualize the significance of updating the content of the socialization process of younger students. Updated priorities have been identified (moral dignity, subjectivity, facilitation, social partnership, online and offline information-centralization) and the relevant content characteristics of the socialization of younger students: a) value and normative orientation in the system of public relations (active and conscious introduction of students to the norms and attitudes of society, as well as to traditional Russian spiritual and moral values); b) activating the subject position of students in the context of expanding the field of their self-realization, self-affirmation and social success (teaching new models of constructive interaction with other people, forming tolerance and the ability to live in a multinational and multicultural environment); c) socio-psychological protection of students in terms of priority of humane pedagogical influence, competent and safe in relation to all participants in educational relations; d) social integration of the possibilities of the education system and the family in the social formation of students (fruitful organization of cooperation between all participants in educational relations as allies and like-minded people in order to achieve a high level of socialization of younger students); e) information awareness and realistic assessment by online students of risks and ways of their timely minimization in the modern world (expanding the range of knowledge about the risk situations that students face in the digital world, forming skills to competently counter destructive online influences).